2018
DOI: 10.1007/s12687-018-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of fragile X checklist and CGG distribution in specialized institutions in Kinshasa, DR Congo

Abstract: Screening for fragile X syndrome (FXS) is essential in children with developmental delay or intellectual disability (ID). In addition, using clinical screening checklists remains of high interest in resource-limited settings. We aimed to gain insight into the prevalence of FXS and the distribution of CGG alleles and to evaluate the usefulness of three checklists in specialized institutions in Kinshasa, DR Congo. We recruited 80 males and 25 females from six specialized institutions in Kinshasa and administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Lubala et al [ 38 ] in Congo found clinical and behavioral phenotyping with checklists reported by Hagerman et al [ 37 ], Maes et al [ 40 ] and Guruju et al [ 39 ] to be helpful. In contrast, Lumaka et al [ 90 ] in Congo, Central Africa, noted that none of the 105 individuals assessed with checklists reported by previous authors had FXS after molecular testing, further highlighting the need for gene testing for suspected cases. The paucity of genetic services in Africa may result in a lack of accurate data on the prevalence of FXS in Africa and hinders efforts to improve diagnosis and treatment of the condition.…”
Section: Epidemiology Of Fxs In Africamentioning
confidence: 89%
See 2 more Smart Citations
“…Lubala et al [ 38 ] in Congo found clinical and behavioral phenotyping with checklists reported by Hagerman et al [ 37 ], Maes et al [ 40 ] and Guruju et al [ 39 ] to be helpful. In contrast, Lumaka et al [ 90 ] in Congo, Central Africa, noted that none of the 105 individuals assessed with checklists reported by previous authors had FXS after molecular testing, further highlighting the need for gene testing for suspected cases. The paucity of genetic services in Africa may result in a lack of accurate data on the prevalence of FXS in Africa and hinders efforts to improve diagnosis and treatment of the condition.…”
Section: Epidemiology Of Fxs In Africamentioning
confidence: 89%
“…Another challenge is the limited access to genetic testing, resources, inadequate healthcare infrastructure and specialized healthcare services in many African countries [ 20 , 21 , 22 , 90 ].…”
Section: Epidemiology Of Fxs In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study to evaluate the prevalence of FXS in central Africa in a systematic way in a high-risk population of individuals attending schools for special education or specialized clinics for persons with ID, not a single case of FXS was diagnosed with molecular testing among 105 individuals (Lumaka et al ., 2019). However, intermediate alleles that are known to be instable have been found in 2/130 chromosomes that were analyzed, suggesting that FXS is very likely to be present in the Congolese population.…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk of expansion of the CGG repeats in a premutation allele to a full mutation overlays the transmission pattern of this syndrome [8,15]. Research on FXS in African population is limited probably due to scarce genomic and genetic services on the continent [16][17][18], and few qualified personnel [19]; only a few scholars have identified families living with FXS through clinical research [20][21][22]. It is likely that with the developing medical genetic services in countries such as Cameroon [18], this situation will gradually improve.…”
Section: Introductionmentioning
confidence: 99%